Attitudes towards English medium instruction courses among second language learners in relation to learning anxiety, learning motivation and learning achievement: a case study at tertiary education / Nurul Farhani Che Ghani - Che Ghani, Nurul Farhani (2015)
The purpose of his paper was to examine second language learners’ attitudes towards English Medium Instruction (EMI) courses at University of Selangor (UNISEL) affectively, behaviorally and cognitively. This study also investigated students’ learning anxiety, students’ learning achievement and students’ learning motivation towards EMI courses. This study used ABC Model of Attitudes (1998) as guidelines to investigate learners’ attitudes towards EMI courses. 100 degree students from Faculty of Computer Science and Information Technology (FCSIT) participated in the study by completing a questionnaire on English Medium Instruction courses. A quantitative method was employed to analyze the collected data, performing statistical procedures of descriptive statistics and Pearson correlation using SPSS. Qualitative interviews were also conducted with six participants to gain insight into the participants’ attitudes towards English Medium Instruction courses. The major findings of the study were as follow: (1) most participants demonstrated positive attitudes towards English Medium Instruction courses affectively, behaviorally and cognitively, (2) there was no significant relationship between students’ learning anxiety and students’ learning achievement towards EMI courses. It was due to the ways lecturer delivering EMI courses to the students. (3) There was a strong positive relationship between students’ learning motivation and students’ learning achievement towards EMI courses. Interview findings revealed that the students faced difficulties to understand jargon words in this course and EMI courses are helpful to improve students’ English proficiency in terms of reading, writing, speaking and listening skills.